Introduction to the New Testament - Godet, Frederic Louis, 1812-1900 (Edinburgh, Scotland T and T Clark, 1894)
Contents : St Paul's Epistles. Includes bibliographical references.
Donated by Dr D.L. Edwards.
Keywords: Bible. N.T. Epistles of Paul -- introductions